Speed of convergence and relocation: New EU member countries catching up with the old - Kari E. O. Alho; Ville Kaitila; Mika Widgrén (The Research Institute of the Finnish Economy (ETLA), 2004)
Economic convergence of the new member countries (NMCs) of the EU towards the incumbent EU countries (EU-15), not only in terms of real income, but also in nominal terms, is of paramount importance for both partners. We build a dynamic CGE model, starting from the Balassa-Samuelson two-sector framework, but modify and enlarge it with, i.a., endogenous capital formation, consumption behaviour and labour mobility to address several other issues like uncertainty, welfare and sustainability in terms of foreign indebtedness. At the same time we evaluate, by endogenising FDI flows, what impact convergence has on the EU-15 and what is the interaction between the two regions through FDI. We find that in a general equilibrium setting fears of adverse effects of a relocation of EU-15 manufacturing to the NMCs are not well founded. – – EU:n uusien jäsenmaiden taloudellinen konvergenssi kohti vanhoja EU-15 -maita, ei ainoastaan reaalisen tulotason, vaan myös hintojen ja palkkojen osalta on tärkeä molemmille osapuolille. Rakennamme kahden tuotantosektorin dynaamisen yleisen tasapainon mallin lähtien liikkeelle Balassa-Samuelson -kehikosta, jota muunnamme ja laajennamme mm. endogeenisilla investoinneilla, kulutuskäyttäytymisellä ja työvoiman liikkeillä, ja tarkastelemme useita kysymyksiä, kuten epävarmuutta, hyvinvointia ja konvergenssiprosessin vakautta ulkomaisen velkaantumisen osalta. Samalla arvioimme endogenisoimalla suorat sijoitukset sitä, mikä on näiden kahden alueen keskinäinen riippuvuus suorien sijoitusten välityksellä ja mikä vaikutus konvergenssilla on EU-15 -maihin. Tulokseksi saamme, että yleisen tasapainon mielessä pelot tuotannon uudelleensijoittamisen kielteisistä vaikutuksista EU-15 - maille eivät ole kovinkaan perusteltuja.
Keywords: F15; F21; F43; 330; Convergence; New Member Countries; EU-15; Konvergenssi; uudet jäsenmaat; EU-15 -maat; Entwicklungskonvergenz; Verarbeitendes Gewerbe; Standortwettbewerb; EU-Staaten; EU-Staaten (Osteuropa)